THE SEMIOTICS MEANING OF BLUE, PINK, AND GREEN IN INDONESIAN DIGITAL PROTEST - Shakila, Raisa Irdina; Luthfiani, Annisa; Natanael, Yolanda Putri; Salsabila, Tri Amanda; Dalimunthe, Fadilah Safrany (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
This study analyzes the symbolic meaning of the colors pink, blue, and green that appeared in digital demonstrations in Indonesia in 2025 using Charles Sanders Peirce's triadic semiotics approach. This approach views signs as a combination of three main elements: representamen (signs), objects (what is signified), and interpretants (the meanings produced). The research method uses qualitative analysis of posts and comments on social media that contain these color symbols. The results show that these colors not only function as visual elements, but also convey social, emotional, and ideological messages that develop dynamically according to the social and political context. Pink symbolizes women's courage, green symbolizes solidarity and justice for workers, while blue represents national consciousness and resistance. The combination of these three colors unites the meanings of courage, solidarity, and resistance as symbols of the people's struggle that lives on in Indonesia's culture of digital protest. This study provides a new perspective on the use of color as a dynamic and contextual medium of political communication in the digital age. Keyword: Semiotic, Digital Protest , Resistance